Antigen-presenting B cells promote TCF-1+ PD1- stem-like CD8+ T-cell proliferation in glioblastoma - Hou, David; Wan, Hanxiao; Katz, Joshua L.; Wang, Si; Castro, Brandyn A.; Vazquez-Cervantes, Gustavo I.; Arrieta, Victor A.; Dhiantravan, Silpol; Najem, Hinda; Rashidi, Aida; Chia, Tzu-yi; Arjmandi, Tarlan; et al. (Frontiers in Immunology, 2024)
Understanding the spatial relationship and functional interaction of immune cells in glioblastoma (GBM) is critical for developing new therapeutics that overcome the highly immunosuppressive tumor microenvironment. Our study showed that B and T cells form clusters within the GBM microenvironment within a 15-m radius, suggesting that B and T cells could form immune synapses within the GBM. However, GBM-infiltrating B cells suppress the activation of CD8+ T cells. To overcome this immunosuppression, we leveraged B-cell functions by activating them with CD40 agonism, IFNγ, and BAFF to generate a potent antigen-presenting B cells named BVax. BVax had improved antigen cross-presentation potential compared to naïve B cells and were primed to use the IL15-IL15Ra mechanism to enhance T cell activation. Compared to naïve B cells, BVax could improve CD8 T cell activation and proliferation. Compared to dendritic cells (DCs), which are the current gold standard professional antigen-presenting cell, BVax promoted highly proliferative T cells in-vitro that had a stem-like memory T cell phenotype characterized by CD62L+CD44- expression, high TCF-1 expression, and low PD-1 and granzyme B expression. Adoptive transfer of BVax-activated CD8+ T cells into tumor-bearing brains led to T cell reactivation with higher TCF-1 expression and elevated granzyme B production compared to DC-activated CD8+ T cells. Adoptive transfer of BVax into an irradiated immunocompetent tumor-bearing host promoted more CD8+ T cell proliferation than adoptive transfer of DCs. Moreover, highly proliferative CD8+ T cells in the BVax group had less PD-1 expression than those highly proliferative CD8+ T cells in the DC group. The findings of this study suggest that BVax and DC could generate distinctive CD8+ T cells, which potentially serve multiple purposes in cellular vaccine development.